2014
DOI: 10.1007/s40140-014-0051-z
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Oxygenation and Management of Hypoxemia During VATS

Abstract: The volume and complexity of thoracic procedures performed with a thoracoscopic approach are steadily increasing. Surgical exposure is paramount for thoracoscopic procedures and requires meticulous lung isolation. In this review, the physiological adaptive mechanisms that occur during one-lung ventilation (OLV) are discussed. Factors that predict the occurrence of hypoxemia during OLV and a structured approach to the treatment of hypoxemia are outlined. Hypoxemia management is formulated in an escalating fashi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In 20% of 2,015 patients that required lung isolation through a DLT, we recorded at least one episode of desaturation during OLV. The incidence in the literature varies from 27% of the 1970s-1990s (23,24) to 5-10% of the most recent studies of Walsh et al (25). This remarkable difference can be explained by the improving expertise, the new surgical and anesthetic techniques, including the use of BRO, newer volatile anesthetics that cause less inhibition of hypoxic pulmonary vasoconstriction (HPV) during OLV (26), and less invasive thoracic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In 20% of 2,015 patients that required lung isolation through a DLT, we recorded at least one episode of desaturation during OLV. The incidence in the literature varies from 27% of the 1970s-1990s (23,24) to 5-10% of the most recent studies of Walsh et al (25). This remarkable difference can be explained by the improving expertise, the new surgical and anesthetic techniques, including the use of BRO, newer volatile anesthetics that cause less inhibition of hypoxic pulmonary vasoconstriction (HPV) during OLV (26), and less invasive thoracic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that the NIVATS and IVATS groups did not experience desaturation. In previous studies, the incidence of desaturation during OLV via the tube was between 4% and 20% (13)(14)(15) .…”
Section: Discussionmentioning
confidence: 94%
“…Results showed that the NIVATS and IVATS groups did not experience desaturation. In previous studies, the incidence of desaturation during OLV via the tube was between 4 and 20% [ 13 15 ].…”
Section: Discussionmentioning
confidence: 99%